Rancang Bangun Buka Tutup Pintu Air Otomatis Pada Irigasi Sawah Berbasis Arduino Dan Monitoring Menggunakan Android - Chomy Dwi Alel; Aswardi Aswardi (Universitas Negeri Padang, 2020)
Irrigation sluice gate is used to stabilize the water stream in agricultural channel. In the traditional agricultural type, the sluice control method is applied with fully human assistance. In this study, the system made to open and close the irrigation gate is controlled automatically based on Arduino Uno and monitor using an android system to ease the human work. This system is made using atmega 328 microcontroller as a central control, flow meter sensor as air flow calculation, water level sensor as air level calculation, Bluetooth HC-05 module which is used as a liaison between tools and android, Android is used as an interface between users and devices, android is also used as the monitoring tool, and dc motors are applied to raise and lower the air door. This system works by connecting the device and Android via Blutooth HC-05 then activated the button of door 1 in the android system, then the motor will work to open door 1 with a speed of 99rpm in 2.24 seconds, the water that comes out will be read by a flow sensor and generate the value of 2. If the setpoint on the flow meter has been reached level 0, the motor will close the gate 1 automatically. Furthermore, when it rains and the water level rise then touch down the water level sensor, it will produce the value of 1 then the motor at door 2 which is a disposal door will open at 99rpm in 2.24 seconds.